Assessing the Factors Influencing Cybersecurity Effectiveness: A PLS-SEM Approach - Sulistio, Sulistio (Pandawan Sejahtera Indonesia, 2023)
In an ever-evolving digital landscape, the imperative of robust cybersecurity measures to safeguard sensitive data, systems, and operations cannot be overstated. This research undertakes a comprehensive evaluation of the intricate factors that collectively contribute to cybersecurity effectiveness within organizational contexts. Employing the Partial Least Squares Structural Equation Modeling (PLS-SEM) methodology, this research dissect the complex relationships among pivotal constructs including Security Measures Effectiveness, Incident Response Capability, Vulnerability Management, User Training Impact, Security Policy Adherence, External Threat Mitigation, Data Protection Effectiveness, and System Resilience. Through data derived from surveys and meticulous assessments, our analysis utilizes PLS-SEM to quantitatively scrutinize how these constructs interconnect and impact the overarching goal of cybersecurity: the proactive prevention, swift detection, and effective mitigation of cyber threats. By elucidating the constructs with the most significant influence, our study not only enhances scholarly discourse but also empowers organizations to refine cybersecurity strategies, strengthen user training initiatives, and implement robust policies in alignment with the ever-adapting threat landscape. Ultimately, this research furnishes organizations with insights to bolster their cybersecurity defenses, fortify digital assets, and counteract the escalating sophistication of cyber threats.